THE STABILITY OF FATTY ACID OMEGA-3 OF SALTED MACKEREL IN VACUUM PACKING - Widodo Farid Ma’ruf (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Salted fist, one of the products od processed fish, is produced by the application of high temperature so that its quality tends to decrease during storage. One of the factors contributing to quality deterioration is the chemical reaction involving lipids such as oxidation and hydrolysis. Oxidation is caused by the presence of and accelerated by other factors such as temperature. This reaction occurs easily in fatty acid omega-3, which is one of a number of unsaturated fatty acids Hydrolysis reaction is caused by lipase enzyme in fish body. Therefore, it is necessary to find an appropriate storage method to prevent lipid deterioration. This research applied low temperature to preserve salted fish. The study was aimed at investigating the influence of low temperature (4oC) as compared to ambient temperature on the stability of fatty acids omega-3 of salted mackerel fish wrapped in vacuum packing. Results showed that omega-3 content in mackerel varied with different storage temperature and period.